Nuclear PKM2 regulates β-catenin transactivation upon EGFR activation - Yang, Weiwei (2011)
The embryonic pyruvate kinase M2 (PKM2) isoform is highly expressed in human cancer. In contrast to the established role of PKM2 in aerobic glycolysis or the Warburg effect(1,2,3), its nonmetabolic functions remain elusive. Here we demonstrate that EGFR activation induces translocation of PKM2, but not PKM1, into the nucleus, where K433 of PKM2 binds to c-Src-phosphorylated Y333 of β-catenin. This interaction is required for both proteins to be recruited to the CCND1 promoter, leading to HDAC3 removal from the promoter, histone H3 acetylation, and cyclin D1 expression. PKM2-dependent β-catenin transactivation is instrumental in EGFR-promoted tumor cell proliferation and brain tumor development. In addition, positive correlations have been identified among c-Src activity, β-catenin Y333 phosphorylation, and PKM2 nuclear accumulation in human glioblastoma specimens. Furthermore, levels of β-catenin phosphorylation and nuclear PKM2 have been correlated with grades of glioma malignancy and prognosis. These findings reveal that EGF induces β-catenin transactivation via a mechanism distinct from that induced by Wnt/wingless(4) and highlight the essential nonmetabolic functions of PKM2 in EGFR-promoted β-catenin transactivation, cell proliferation, and tumorigenesis.